2022
DOI: 10.1007/s12209-022-00341-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Large-Area Perovskite Photovoltaic Modules

Abstract: Perovskite solar cells (PSCs) have undergone a dramatic increase in laboratory-scale efficiency to more than 25%, which is comparable to Si-based single-junction solar cell efficiency. However, the efficiency of PSCs drops from laboratory-scale to large-scale perovskite solar modules (PSMs) because of the poor quality of perovskite films, and the increased resistance of large-area PSMs obstructs practical PSC applications. An in-depth understanding of the fabricating processes is vital for precisely controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 183 publications
0
8
0
Order By: Relevance
“…Unfortunately, the application of surface termination for organic–inorganic hybrid perovskite films is restricted because commonly used organic ammonium cations easily induce the formation of LD perovskites by fast organic cation substitution. The sensitivity of this strategy to operating conditions, such as temperature (less than 50 °C) and processing window (less than 1 min), makes it difficult to meet the requirements of mass applications [20–22] . To overcome such dilemma, several strategies have been developed.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the application of surface termination for organic–inorganic hybrid perovskite films is restricted because commonly used organic ammonium cations easily induce the formation of LD perovskites by fast organic cation substitution. The sensitivity of this strategy to operating conditions, such as temperature (less than 50 °C) and processing window (less than 1 min), makes it difficult to meet the requirements of mass applications [20–22] . To overcome such dilemma, several strategies have been developed.…”
Section: Figurementioning
confidence: 99%
“…The sensitivity of this strategy to operating conditions, such as temperature (less than 50 °C) and processing window (less than 1 min), makes it difficult to meet the requirements of mass applications. [20][21][22] To overcome such dilemma, several strategies have been developed. By tuning structural isomers of phenylenediammonium, ortho-(phenylene)di-(ethylammonium) iodide was designed to prevent the formation of two-dimensional (2D) perovskite and show significant enhancements in the efficiency and stability of PSCs.…”
mentioning
confidence: 99%
“…As an emerging class of semiconducting materials, metal-halide perovskites have attracted extensive interest due to their outstanding optoelectronic property, band gap tunability, and solution processability. These features allow for their successful application in LEDs, and external quantum efficiency (EQE) values of over 20% have been reached. In recent years, by breaking the inversion symmetry in structure, in conjunction with its strong spin–orbit coupling (SOC), perovskite could acquire amazing spin-polarized-related effects, , which makes perovskites attractive candidates for spin-LEDs. By exploiting the spin degree of freedom instead of, or in addition to, the charge, spin-LEDs afford reduced power consumption and higher speed compared with conventional LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…So far, previous studies have reported various coating methods for large-area modules, [4][5][6][7][8][9][10][11][12][13][14] proper module designs, [15,16] and interconnection methods. [4,[17][18][19][20][21][22] Also, monolithic interconnection plays a critical role in solar module performance, and therefore, interconnection methods such as mechanical scribing and laser scribing have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%